2014
DOI: 10.1681/asn.2013030233
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis Reveals the Complexity of the Human Glomerular Extracellular Matrix

Abstract: The glomerulus contains unique cellular and extracellular matrix (ECM) components, which are required for intact barrier function. Studies of the cellular components have helped to build understanding of glomerular disease; however, the full composition and regulation of glomerular ECM remains poorly understood. We used mass spectrometry-based proteomics of enriched ECM extracts for a global analysis of human glomerular ECM in vivo and identified a tissue-specific proteome of 144 structural and regulatory ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
213
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(234 citation statements)
references
References 45 publications
9
213
0
2
Order By: Relevance
“…These findings are very similar to the tissue-derived glomerular ECM interactome, which identified a core of highly connected structural components. 15 Overall, these data suggest that qualitative differences between GEnC and podocyte ECMs do not affect the core organization of the ECM.…”
Section: Glomerular Cells In Vitro Exhibit Differential Ecm Protein Smentioning
confidence: 73%
See 2 more Smart Citations
“…These findings are very similar to the tissue-derived glomerular ECM interactome, which identified a core of highly connected structural components. 15 Overall, these data suggest that qualitative differences between GEnC and podocyte ECMs do not affect the core organization of the ECM.…”
Section: Glomerular Cells In Vitro Exhibit Differential Ecm Protein Smentioning
confidence: 73%
“…There was considerable (55%) overlap between proteins detected in GEnC and podocyte ECMs, suggesting a common core of ECM proteins, but cell typespecific proteins were also identified ( Figure 2B). Furthermore, 44% of proteins in the recently described in vivo glomerular ECM proteome 15 were identified in cell-derived ECMs ( Figure 2B). Statistical analysis of all identified proteins in the cell-derived ECM samples revealed differential ECM protein synthesis between GEnCs and podocytes ( Figure 2C, Supplemental Table 3).…”
Section: Glomerular Cells In Vitro Exhibit Differential Ecm Protein Smentioning
confidence: 81%
See 1 more Smart Citation
“…Nothing is known about such mechanisms in the kidney allograft. In glomeruli, global analyses of ECM has suggested this structure to be more complex than anticipated (96,351).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…miR-378a-3p was described to target nephronectin (NPNT) in osteoblasts [19]. Mass spectrometry-based proteomics of extracellular glomerular matrix extracts in humans identified that NPNT expression is specifically localized in the GBM [20]. NPNT also is a ligand of integrin a8-b1 during kidney development [21][22][23].…”
mentioning
confidence: 99%